Perbedaan Kesegaran Jasmani pada Anak Usia Sekolah Yang Anemia dan Non Anemia di SD Negeri Banyuanyar III Kota Surakarta - Sholihah, Latifah Arifatush, Ir. Listyani Hidayati, M.Kes, Susi Dyah Puspowati, SP., M.Si (2013)
Background. Anemic is a condition with a hemoglobin count below the normal value, estimated at about 50% the cause of anemia is iron deficiency. Anemia is generally caused pallor, weakness, fatigue, dizziness, decreased appetite, decreased physical fitness, decreased ability to work, decreased immunity. This will affect to the level of physical fitness which is very important in achieving optimal growth and development in childhood. Objective. This study aimed to determine differences of physical fitness in anemic and non-anemic school-aged children at SDN Banyuanyar Surakarta III. Research Methods. This type of research is an observational study with cross sectional analytic. Subjects are taken using a stratified random sampling with the number of study subjects is 80. The rate of Hb obtained using cyanmethemoglobin methods with HemoCue instrument, while the physical fitness test is obtained by the method of aerobic running 1600 m. The different test used Mann Whitney U-test. Results. Out of the 80 research subjects consisting of 47 men and 33 women,its known that anemic students had excellent physical fitness category as 0%, which is 2.5% better category, the category is quite as much as 12.5%, which is 15% less categories and category once as much as 70% less, while the non anemic students are excellent physical fitness category 2.5%, 7.5% either category, the category is quite and less each category as much as 12.5% and as much as 65% less once. Statistical test results obtained (p = 0.76) whose value is p >0.05. Conclusion. There is no difference of physical fitness in anemic and non-anemic children at SDN Banyuanyar III.